Estudo da evolução da paisagem da área do município de Linhares (ES) nos anos de 1985 e de 2013/2014, por meio das métricas - Batalha, Marta Leite Oliver (2014)
This research aim about the study of the evolution of the landscape area that makes up the city of Linhares (ES) in the years of 1985 and of 2013/2014, which is the largest municipality in the state of Espírito Santo. By means of digital image processing of LANDSAT 5 and 8, the classification of land use and land cover of the study area was performed. Also used the images on RapdEye satelite for accuracy of digital image classification. From the results collected for use and cover land of the landscape matrices were set for 1985 and 2013/2014, as well as evaluated the spots that make up the array. The landscape metrics using the statistical tool Fragstats were applied, enabling the calculation of landscape indices in order to assess the qualitative and quantitative evolution of the landscape of the municipality of Linhares.